ADVICES ON SEARCH AND CRITICAL APPRAISAL OF BIOMEDICAL LITERATURE PART I, GENERAL WORKFLOW - Dauletbayev, Nurlan (Interdisciplinary Approaches to Medicine, 2020)
Both physician-scientists and practicing physicians regularly experience the need to browse, select, and critically appraise the current biomedical literature. There have been many useful reviews on each of the aforementioned topics. Still, having a unified and coherent workflow, feasible to fit into a busy clinical routine, would surely be appreciated by physicians. In addition, many of the aforementioned reviews have been written to target the audience in developed countries. In contrast, particularities of the access to the literature in developing countries (or economies in transition) have been addressed less frequently. Finally, new computational approaches, including machine translation and automated text mining, are rapidly emerging. These are indeed worthy addressing as the initiatives that could provide a great help to practicing physicians for rapid, yet comprehensive literature appraisals.The present review aims to provide physicians with the workflow and methodological recommen- dation on browsing, selecting, and critical appraisal of the biomedical literature, with the specific focus on patient- and disease-oriented publications.The review further aims to overcome the aforementioned limitations of the previously published literature on this subject.